Synergistic prostaglandin E synthesis by myeloid and endothelial cells promotes fetal hematopoietic stem cell expansion in vertebrates. (4th August 2022) - Cacialli, Pietro; Mailhe, Marie‐Pierre; Wagner, Ingrid; Merkler, Doron; Golub, Rachel; Bertrand, Julien Y
Abstract: During development, hematopoietic stem cells (HSCs) are produced from the hemogenic endothelium and will expand in a transient hematopoietic niche. Prostaglandin E2 (PGE2) is essential during vertebrate development and HSC specification, but its precise source in the embryo remains elusive. Here, we show that in the zebrafish embryo, PGE2 synthesis genes are expressed by distinct stromal cell populations, myeloid (neutrophils, macrophages), and endothelial cells of the caudal hematopoietic tissue. Ablation of myeloid cells, which produce the PGE2 precursor prostaglandin H2 (PGH2), results in loss of HSCs in the caudal hematopoietic tissue, which could be rescued by exogeneous PGE2 or PGH2 supplementation. Endothelial cells contribute by expressing the PGH2 import transporter slco2b1 and ptges3, the enzyme converting PGH2 into PGE2. Of note, differential niche cell expression of PGE2 biosynthesis enzymes is also observed in the mouse fetal liver. Taken altogether, our data suggest that the triad composed of neutrophils, macrophages, and endothelial cells sequentially and synergistically contributes to blood stem cell expansion during vertebrate development. Synopsis: The microenvironmental signals supporting hematopoietic stem cell (HSC) expansion during development in the hemogenic endothelium and specific niche cell contributions remain debated. Here, biosynthesis of the critical HSC control factor prostaglandin E2 (PGE2) is shown to be functionally divided across stromal cell populations, shedding new light on stem cell niche cooperation in establishing the blood system. PGE2 production enzymes are distinctly expressed in neutrophils, myeloid and endothelial cells in the zebrafish caudal hematopoietic niche. Depletion of the transporter Slco2b1 or myeloid cells impairs import of the PGE2 precursor PGH2 into endothelial cells and HSC expansion, which can be rescued by exogeneous PGE2. Niche distribution of PGE2 biosynthesis enzymes is conserved in the mouse fetal liver. Abstract : Stromal cell collaboration in the embryonic hematopoietic niche preserves production of the stem cell specification factor prostaglandin E2 .